Investigation into low density porous concrete penetrability by air / Mažo tankio akytojo betono oro laidumo tyrimai - Laukaitis, Antanas; Kunskaitė, Laima J. (Journal of Civil Engineering and Management, 1996)
Low-density (250–350 kg/m3) porous concrete has good thermal insulation and acoustical properties. However, the determination of these properties requires a lot of time and is rather costly.Changes in these properties can be determined, if the porous concrete air penetrability, which can be simply found, is known.This paper deals with porous concrete made using Portland cement binder and a binder mixture (lime + Portland cement), as well as with foam concrete air penetrability coefficient value dependency on its density and water/dry solids ratio V/K.The raw materials composition is given in Table 1. Fig. 1 represents the air penetrability determination apparatus scheme.Air penetrability increases with a decrease of density in porous concrete sample. For example, when V/K=0.6 and product density decreases from 490 to 310 kg/m3, the air penetrability coefficient increases from 2.5·10−7to 13.1·10−7 m3/m·S·Pa.Porous concrete air penetrability increases with an increase in V/K (Fig. 2.). The air penetrability coefficient increases from 6·6·10−7 to 12.8·10−7 m3/m·S·Pa when the product density is 350 kg/m3 and V/K changes from 0.5 to 0.7. Changes in V/K have a greater influence on low density porous concrete air penetrability. That is why, when slowly hydrating Portland cement is used for porous concrete production, foaming formation mixture temperature is not high, it binds and is cured very slowly. For higher density product pore structures such a slow curing process does not have any effects, because small, spherical pores prevail.When the water content is increased in the formation mixture, a change in product porous structure is observed, because larger deformed coupled pores are formed and therefore the air penetrability increases. An air penetrability dependency on product density and V/K regression equation (3) is given.Air penetrability coefficients of porous concrete made using a mixed binder (lime + Portland cement) are given in Table 2. It has been established, that a 20% Portland cement equivalent amount of lime in the binder mixture according to equation 1 and when the V/K ratio increased from 0.52 to 0.65, the some density product air penetrability coefficient of equal density products increased by 3 times, while the lime content in the binder increased from 20 to 80% from formation mixture samples with V/K ratio =0.52.Air penetrability of porous concrete made using a mixed binding material also depends on concrete density and formation mixture V/K ratio (Fig. 3.).Cellular concrete air penetrability coefficient values are given in Fig. 4. Cellular concrete differs from porous concrete, because its air penetrability coefficient values decrease with an increase in V/K ratio. This is the reason why cellular concrete air penetrability coefficients are lower than those of porous concrete. Cellular concrete air penetrability coefficient dependency on product density and V/K ratio is expressed by equation 4.Article in Lithuanian.First Published Online: 26 Jul 2012